Taste Testing of Some Cooked Foods kept in the Warmer - NOGUCHI, Noriko; MATSUURA, Hiroshi; KOBAYASHI, Keiko (Journal of Home Economics of Japan, 1969)
A preference test and a choice test were conducted to determine likes and dislikes for the taste of some cooked foods which had been kept in the warmer for certain hours. The following results were obtained : 1. Nikudango (meat balls) which had been kept for 2 hours in room temperature and 2 hours in the warmer (6667°C), respectively, were less preferred than the same dish tasted immediately on completion of cooking. 2. Chahan (sauté rice) which had been kept for 2 hours in the warmer (6870°C) was less preferable than the one that was tasted immediately on completion of cooking. 3. There was no difference in taste preference between pork stew which had been kept in the warmer (72°C) for 4.5 hours and that which was tasted soon after the cooking. Chawan-Mushi (egg-custard) showed the same results as pork stew. 4. The taste of the cooked rice and Miso-soup which had been kept in the warmer (68° and 62°C respectively) for 3 hours did not show any differences erences in the test from the taste of those which were hot from the pan.